(untitled) (Stamford Journal of Microbiology, 2013)
Lactic acid bacteria (LAB) are regarded as effective probiotic organisms and used with a view of augmenting the safety of the food. In the present study, five food items (meat, fish, apple, milk and carrot) were selected having high nutritive and economic value, assumptive of harboring lactic acid bacteria. A total of 29 LABs were isolated from 5 different samples after 2 batches of fermentation. All of the isolates were then tested against 4 most frequently encountered pathogens, Staphylococcus aureus, Escherichia coli, Salmonella typhimurium, and Vibrio cholerae. Among all these isolates, those from meat and fish samples showed positive average inhibitory coefficient (AIC) against two target pathogens, while those from milk and carrot showed positive AIC against three pathogens each, and isolates from apple revealed positive AIC against all four pathogens used. More than 50% of the isolates were found to inhibit or mask the pathogens when allowed to grow along with the individual pathogen on the each tested food item. Out of 29 isolates, 17 were found to successfully inhibit Escherichia coli, 11 worked against S. aureus, 11 against S. typhimurium, and 13 showed significant effect against V. cholerae. Among these isolates ML4, ML8, AP5 and CR3 most notably showed the potential to inhibit or mask at least three of the target pathogenic strains. DOI: http://dx.doi.org/10.3329/sjm.v2i1.15203 Stamford Journal of Microbiology, Vol.2(1) 2012: 6-9